Proceedings of the 13th International Conference on World Wide Web 2004
DOI: 10.1145/988672.988676
|View full text |Cite
|
Sign up to set email alerts
|

Impact of search engines on page popularity

Abstract: Recent studies show that a majority of Web page accesses are referred by search engines. In this paper we study the widespread use of Web search engines and its impact on the ecology of the Web. In particular, we study how much impact search engines have on the popularity evolution of Web pages. For example, given that search engines return currently "popular" pages at the top of search results, are we somehow penalizing newly created pages that are not very well known yet? Are popular pages getting even more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
147
2
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(156 citation statements)
references
References 20 publications
1
147
2
6
Order By: Relevance
“…This is justified in real settings by observing, for example, that sites that are highly ranked by search engines have more visibility, and therefore have a better chance to be linked from other sites, leading to even higher visibility [132]. The model can also be extended to allow for link deletions [255].…”
Section: Preferential Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This is justified in real settings by observing, for example, that sites that are highly ranked by search engines have more visibility, and therefore have a better chance to be linked from other sites, leading to even higher visibility [132]. The model can also be extended to allow for link deletions [255].…”
Section: Preferential Attachmentmentioning
confidence: 99%
“…An increasing fraction of traffic enters a website by a redirection from a search engine, rather than by browsing through the site's home page (data for blogs indicates that search engines lead to a third of all read requests, higher than any other individual source [192]). Thus pages that rank high on search engines tend to become ever more popular, whereas new pages that are not indexed have a much harder time [132].…”
Section: Page Popularitymentioning
confidence: 99%
“…In [12], Cho et al examined the impact of search engines on the popularity of web pages. In [13], Fortunato et al found that search engines avoided a theoretical vicious cycle of popularity, and instead had a tendency to send users to less popular pages than they would have otherwise found.…”
Section: Related Workmentioning
confidence: 99%
“…Identification of web communities was explored in [23,12]. The effect that search engines have on page popularity was discussed in [7].…”
Section: Introductionmentioning
confidence: 99%